2022
DOI: 10.1007/s00784-022-04442-9
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentation during the second stage of periodontal therapy: a European survey

Abstract: Objectives To gather practice-based information about instrumentation during the second stage of periodontal therapy among the members of the European Federation of Periodontology. Methods This survey was conducted to investigate periodontal instrumentation (e.g., frequency, instruments, their maintenance) during the second stage of periodontal therapy. Results Questionnaires from 2008 responders actively involved in periodontal therapy (general dental practitioners, periodontists, and dental hygienists) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Due to these advantages, the ultrasonic scaler has become a widely accepted instrument in clinics. A recent practice-based study showed that the application frequency of both manual and ultrasonic scaler was similar in periodontal therapy, with 94.4% of periodontists combining both methods [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to these advantages, the ultrasonic scaler has become a widely accepted instrument in clinics. A recent practice-based study showed that the application frequency of both manual and ultrasonic scaler was similar in periodontal therapy, with 94.4% of periodontists combining both methods [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disease leads to significant cellular damage and tissue loss which eventually culminates in bone loss (Hajishengallis, 2022;Zenobia and Darveau, 2022;Vitkov et al, 2023). The extent of hard and soft tissue loss determines the treatment strategies; however, mechanical debridement remains the cornerstone of periodontal treatment which turns the inflammatory state of the periodontium to a resolving state (Albeshri and Greenstein, 2022;Laleman et al, 2022). Periodontal treatment not only involves elimination of inflammatory and bacterial component from the diseased tooth supporting tissues, but also comprises of regeneration of deteriorated periodontal structures in amenable cases which serves as the bedrock to principles of tissue engineering that engages application of appropriate cells, growth factors and scaffolds Tavelli et al (2022), Yi et al (2022), Sopi et al (2023).…”
Section: Introductionmentioning
confidence: 99%